A Comparison of Dielectric Properties of Palm Oil with Mineral and Synthetic Types Insulating Liquid under Temperature Variation - Rajab, Abdul; Sulaeman, Aminuddin; Sudirham, Sudaryatno; Suwarno, Suwarno (Journal of Engineering and Technological Sciences, 2011)
Mineral  oil  is  known  to  have  a  low  biodegradability  level  and  high susceptibility to the fire. These conditions motivate many researchers to look for alternative sources for insulating oil. One of the alternative liquid is palm oil. To verify the suitability of using palm oil as an insulating liquid, it is important to make dielectric properties comparison with the commonly used insulating liquid. This paper presents comparison of temperature effect on dielectric properties of palm  oil  with  mineral  type  insulating  liquid  and  silicone  oil.  The  measured parameters  were  breakdown  voltage,  dissipation  factor  (tan  δ),  and  dielectric constant.  Breakdown  voltage  measurement  was  performed  in  accordance  with IEC  156  standard,  whereas,  the  dissipation  factor  and  dielectric  constant measurement  were  conducted  based  on  IEC  60247  standard  test  methods.  The results  showed  that  variations  of  dielectric  properties  of  palm  oil  to  the temperature change, in general, have the same tendency with those of commonly used insulating liquids i.e. mineral oil and silicone oil. Breakdown voltages and dissipation  factors  of  all  tested  oils  were  increased,  while  their  dielectric constants were slightly decreased with the increase of temperature.